Small and Medium Enterprises in Algeria- Between Reality and the Hope for the Future – - Miloudi, Oum elkheir; Boukhedouni, Ouahiba (Finance and Business Economies Review, 2021)
The study aims to diagnose the reality of small and medium enterprises and what is expected to be achieved in the future by revealing obstacles and difficulties that prevent them from being promoted and achieving their future goals while presenting the solutions proposed by the trustees to eliminate financial, organizational and managerial restrictions for their development and development to contribute to economic and social development, To address the various aspects related to the study, a descriptive analytical approach was used to present and analyze all aspects related to the reality of small and medium enterprises in Algeria. The results showed that, despite all the problems encountered and still facing small enterprises, they still play an essential and important role in the national economy by creating new jobs and providing added value in all sectors. Despite the development in the number of small enterprises and construction that appears every year, these institutions are still It suffers from problems and obstacles preventing it from continuing, and this is what we have noticed through the statistics of the deaths of small enterprises that were written off in 2018, which were estimated at 25,63 percent of the total.